A validated 1H NMR method for the determination of the degree of deacetylation of chitosan - Lavertu, M.; Xia, Z.; Serreqi, A. N.; Berrada, M.; Rodrigues, A.; Wang, D.; Gupta, A.
A method for the determination of the degree of deacetylation (DDA)of chitosan by 1H NMR spectroscopy has been formally validated. Chitosans with DDA ranging from 48 to 100 percent have been used for the validation. The method is found to be simple, rapid and more precise than other known techniques like IR or titration for percentDDA measurements. The precision, ruggedness, robustness, specificity, stability and accuracy of the technique are discussed in this paper.
Keywords: CHITOSAN; CHITIN; PH-SENSITIVE; IR; 1H NMR; DEGREE OF DEACETYLATION